First report on phytoplankton communities of Barishal City, Bangladesh - Chakraborty, Shaswati; Karmaker, Dipalok; Das, Subroto Kumar; Hossen, Riyad (Current Botany, 2020)
Phytoplanktons, also called microalgae, are microscopic photosynthetic living organisms that generally found in aquatic environments. Although they are considered as the most important primary producers and bioindicators of aquatic ecosystems, there was no previous report found for Barishal City about these tiny organisms. Consequently, the present study selected 10 freshwater reservoirs from the city to investigate phytoplankton communities and listed 110 taxa under 4 phyla, 7 classes, 18 orders, 24 families and 49 genera. The distribution of Chlorophytes was abundant relatively in terms of species number (45 taxa) followed by Euglenophytes, Chlorophytes and Cyanophytes in this area. Only Euglenaceae possessed one-third of the total species of this report. Among all stations, the highest number of taxa was recorded from station 2 and according to nine biodiversity indices, the station 2 and 9 showed comparatively good results. All of the recorded taxa were previously mentioned by different authors from Bangladesh.